Factor That Influences the Reduction of Plastic Bag Usage Among Universiti Tun Hussein Onn Malaysia (UTHM) Students - Pakir Mohamed, Mohamed Ismail; Wong Leh Ming (Research in Management of Technology and Business, 2021)
Nowadays, plastic bags are widely used in the world including in Malaysia. Malaysia’s environmental problem related to plastic waste has been ranked 8th globally, due to plastic waste mismanagement. In UTHM, it was reported that the three highest waste compositions generated by its residential college cafeteria were food waste, general waste, and plastic waste and UTHM students preferred to use single-use plastic for take-away food. Therefore to resolve the issues, it is important to identify the factors that influence UTHM students’ intention toward the reduction of plastic bag usage. This study uses the Theory of Planned Behavior (TPB) model to determine the factors that influence the intention to reduce plastic bag usage. A quantitative method using a survey approach was deployed were 267 students of the Faculty of Technology Management and Business, UTHM, responded to the questionnaires distributed via an online survey. Descriptive analysis using Statistical Package for Social Science (SPSS) revealed that attitude, subjective norm, perceived behavioral control significantly influence the consumer’s intention to reduce plastic bag usage and attitude is the most influential factor affecting the consumer’s intention to reduce plastic bag usage. Therefore it can be concluded that plastic waste can be reduced if the right attitude can be instilled among Malaysian in this case university among students. It is also recommended that an in-depth study should be conducted to further understand e the right type of attitude needed to be instilled